Sovereignty at Sea : U.S. Merchant Ships and American Entry into World War I - Carlisle, Rodney P. (Book collections on Project MUSE., 2009)
This book demonstrates that, although President Woodrow Wilson worked to maintain United States neutrality during World War I, his administration's policies resulted in a decision by Germany to unleash unrestricted submarine warfare against all shipping bound for Britain, France, or Italy in the Atlantic.